Learning from alcohol (policy) reforms in the Northern Territory (LEARNT): protocol for a mixed-methods study examining the impacts of the banned drinker register. Issue 4 (1st April 2022) - Miller, Peter; Coomber, Kerri; Smith, James; Livingston, Michael; Stevens, Matthew; Guthridge, Steven; Room, Robin; Wright, Cassandra J C; Rung, Daile; Clifford, Sarah; Baldwin, Ryan; Das, Sumon; et al.
Abstract : Introduction: The Banned Drinker Register (BDR) was reintroduced in the Northern Territory (NT) in September 2017. The BDR is a supply reduction measure and involves placing people who consume alcohol at harmful levels on a register prohibiting the purchase, possession and consumption of alcohol. The current study aims to evaluate the impacts of the reintroduction of the BDR, in the context of other major alcohol policy initiatives introduced across the NT such as Police Auxiliary Liquor Inspectors and a minimum unit price for alcohol of US$1.30 per standard drink. Methods and analyses: The Learning from Alcohol (policy) Reforms in the Northern Territory project will use a mixed-methods approach and contain four major components: epidemiological analysis of trends over time (outcomes include health, justice and social welfare data); individual-level data linkage including those on the BDR (outcomes include health and justice data); qualitative interviews with key stakeholders in the NT (n≥50); and qualitative interviews among people who are, or were previously, on the BDR, as well as the families and communities connected to those on the BDR (n=150). The impacts of the BDR on epidemiological data will be examined using time series analysis. Linked data will use generalised mixed models to analyse the relationship between outcomes and exposures, utilising appropriate distributions. Qualitative data will be analysed using thematic analysis. Ethics and dissemination: Ethics approvals have been obtained from NT Department of Health and Menzies School of Health Research Human Research Ethics Committee (HREC), Central Australia HREC and Deakin University HREC. In addition to peer-reviewed publications, we will report our findings to key organisational, policy, government and community stakeholders via conferences, briefings and lay summaries.